APPLICATION OF THE NURSING MODEL "PRIMARY NURSING" TO THE BONE MARROW TRANSPLANT SERVICE - Mariana Bertotti Mendes Nunes; Marilene Loewen Wall; Fátima Silvana Furtado Gerolin; Nen Nalú Alves das Mercês; Mariluci Hautsch Willig; Juliane Dias Aldrighi; Talita Wérica Borges Figueiredo (Universidade Federal do Paraná, 2019)
Objective: To describe the application of the nursing model "Primary Nursing" to patients submitted to hematopoietic stem cell transplantation.Method: Convergent-care research conducted from June to December 2016 with 20 nursing professionals from the Bone Marrow Transplant Service of a Brazilian Public Hospital. The results were obtained with the administration of a semi-structured interview. Thematic analysis described by Creswell was used in data analysis.Results: Six thematic categories based on the applicability of the Primary Nursing model emerged, as follows: Ambience and care process; Knowing the patient; Interpersonal relations; Favorable and unfavorable aspects; Organization of the care process; and Nursing Process.Conclusion: The study reports improvements and difficulties in the nursing care process with the application the Primary Nursing model, but proved above all to be a viable nursing model for the care of patients submitted to hematopoietic stem cell transplantation.